The Spectral Nature of Earth’s Reflected Radiation: Measurement and Science Applications - Stephens, Graeme; Kalashnikova, Olga; Gristey, Jake J.; Pilewskie, Peter; Thompson, David R.; Huang, Xianglei; Lebsock, Matthew; Schmidt, Sebastian (Frontiers in Remote Sensing, 2021)
This paper introduces the aerosol, clouds, convection and precipitation (ACCP) program that is currently in the process of defining a number of measurement objectives for NASA that are to be implemented toward the end of the current decade. Since a (solar) visible-shortwave infrared (VSWIR) spectrometer is being considered as part of the ACCP architecture, illustrations of the different ways these measurements will contribute to this program and how these measurements can be expected to advance the science objectives of ACCP are highlighted. These contributions range from 1) constraining cloud radiative process and related estimates of radiative fluxes, 2) scene discrimination, 3) providing aerosol and cloud optical properties, and 4) providing other enhanced information such as the phase of water in clouds, and total column water vapor. The spectral measurements also offer new capabilities that will further enhance the ACCP science such as the discrimination of dust aerosol and the potential for the vertical profiling cloud droplet size in shallow clouds.